Establishing the selective phospholipid membrane coordination, permeation and lysis properties for a series of 'druggable' supramolecular self-associating antimicrobial amphiphiles. Issue 33 (10th August 2022) - Boles, Jessica E.; Bennett, Charlotte; Baker, Jennifer; Hilton, Kira L. F.; Kotak, Hiral A.; Clark, Ewan R.; Long, Yifan; White, Lisa J.; Lai, Hin Yuk; Hind, Charlotte K.; Sutton, J. Mark; Garrett, Michelle D.; et al.
Abstract : A combination of computational and synthetic phospholipid vesicle/nanodisc assays are used to investigate the mode of action for a class of antimicrobial agents, while a range of DMPK studies establish agent druggability. Abstract : The rise of antimicrobial resistance remains one of the greatest global health threats facing humanity. Furthermore, the development of novel antibiotics has all but ground to a halt due to a collision of intersectional pressures. Herein we determine the antimicrobial efficacy for 14 structurally related supramolecular self-associating amphiphiles against clinically relevant Gram-positive methicillin resistant Staphylococcus aureus and Gram-negative Escherichia coli . We establish the ability of these agents to selectively target phospholipid membranes of differing compositions, through a combination of computational host:guest complex formation simulations, synthetic vesicle lysis, adhesion and membrane fluidity experiments, alongside our novel 1 H NMR CPMG nanodisc coordination assays, to verify a potential mode of action for this class of compounds and enable the production of evermore effective next-generation antimicrobial agents. Finally, we select a 7-compound subset, showing two lead compounds to exhibit 'druggable' profiles through completion of a variety of in vivo and in vitro DMPK studies.